The interaction of amyloid and tau on decreased cortical neurite density in preclinical Alzheimer's disease: Neuroimaging / Optimal neuroimaging measures for early detection. (7th December 2020) - Vogt, Nicholas M; Hunt, Jack F.V.; Adluru, Nagesh; Van Hulle, Carol A; Chin, Nathaniel A.; Carlsson, Cynthia M.; Ma, Yue; Asthana, Sanjay; Johnson, Sterling C.; Zetterberg, Henrik; Alexander, Andrew L; Blennow, Kaj; et al.
Abstract: Background: Both MCI and AD dementia are associated with decreased cortical microstructure as measured by neurite orientation dispersion and density imaging (NODDI). Specifically, in MCI, neurite density index (NDI) – but not cortical thickness – is decreased in several key AD regions, suggesting NODDI may be more sensitive than conventional structural imaging for detecting early neurodegenerative changes. Given that AD pathology accumulates for years before cognitive and clinical symptoms arise, in this study, we tested the hypothesis that cognitively unimpaired individuals with greater AD pathology (as measured in CSF) will have decreased cortical microstructure in AD signature brain regions. Method: 219 cognitively unimpaired individuals (66.8±7.5 yrs, 58.9% female, 38.9% APOE4‐positive) underwent MRI (multi‐shell diffusion‐weighted for NODDI microstructure; T1‐weighted for cortical thickness) as well as CSF AD biomarker quantification (Aβ40, Aβ42, and pTau via ELISAs). The NODDI model was fit using optimized parameters for GM (intracellular parallel diffusivity=1.1μm 2 /ms), and cortical thickness (CT) was calculated using CAT12. Mean NDI and CT were extracted from a bilateral composite AD signature region as well as individual subregions (Fig1A). Linear regression models (controlling for age and sex) tested both main effects and the interaction of CSF Aβ42 /Aβ40 and pTau levels on cortical measures (separate models for NDI and CT). Result: While there were no main effects of CSF Aβ or pTau levels on NDI or CT, there was a significant Aβ‐by‐pTau interaction on NDI in the composite AD signature region, such that individuals with higher burden of amyloid showed lower NDI as a function of pTau (Fig1B). Notably, this interaction was not observed for cortical thickness. Examining individual subregions showed that this interaction effect was observed bilaterally and was strongest in inferior parietal, inferior temporal, and fusiform subregions (Fig1C&D). Conclusion: In cognitively unimpaired individuals with higher amyloid burden, higher pTau was associated with lower NDI – but not thickness – in AD signature cortical regions. These results suggest that amyloid alone (in the absence of tau pathology) is not associated with microstructural changes, and that NDI is a particularly sensitive marker for early AD‐related cortical changes occurring prior to gross atrophy or development of cognitive impairment.